2015
DOI: 10.1097/md.0000000000000905
|View full text |Cite
|
Sign up to set email alerts
|

Strong Negative Interference by Calcium Dobesilate in Sarcosine Oxidase Assays for Serum Creatinine Involving the Trinder Reaction

Abstract: The vasoprotective drug calcium dobesilate is known to interfere with creatinine (Cr) quantifications in sarcosine oxidase enzymatic (SOE) assays. The aim of this study was to investigate this interference in 8 different commercially available assays and to determine its clinical significance.In in vitro experiments, interference was evaluated at 3 Cr levels. For this, Cr was quantified by SOE assays in pooled serum supplemented with calcium dobesilate at final concentrations of 0, 2, 4, 8, 16, 32, and 64 μg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Knowledge of the reliability of such a portable device may help the investigator on‐site, for example during roadside testing, to decide if an additional blood test to detect drugs of abuse is advisable. We refrained from testing the urine samples with an enzymatic assay using the Trinder Reaction, as various substances such as N‐acetylcysteine (NAC), calcium dobesilate, acetaminophen and the metabolite N‐acetyl‐p‐benzoquinone, metamizole, and the metabolites 4‐aminoantipyridine (4‐AAP) and 4‐methylaminoantipyrine (4‐MAP) cause falsified results for Trinder‐based assays . Acetaminophen and metamizole are often present in the studied population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of the reliability of such a portable device may help the investigator on‐site, for example during roadside testing, to decide if an additional blood test to detect drugs of abuse is advisable. We refrained from testing the urine samples with an enzymatic assay using the Trinder Reaction, as various substances such as N‐acetylcysteine (NAC), calcium dobesilate, acetaminophen and the metabolite N‐acetyl‐p‐benzoquinone, metamizole, and the metabolites 4‐aminoantipyridine (4‐AAP) and 4‐methylaminoantipyrine (4‐MAP) cause falsified results for Trinder‐based assays . Acetaminophen and metamizole are often present in the studied population.…”
Section: Introductionmentioning
confidence: 99%
“…We refrained from testing the urine samples with an enzymatic assay using the Trinder Reaction, as various substances such as N-acetylcysteine (NAC), calcium dobesilate, acetaminophen and the metabolite N-acetyl-pbenzoquinone, metamizole, and the metabolites 4aminoantipyridine (4-AAP) and 4-methylaminoantipyrine (4-MAP) cause falsified results for Trinder-based assays. [5][6][7] Acetaminophen and metamizole are often present in the studied population.…”
Section: Introductionmentioning
confidence: 99%
“…But research using big data suggests that CaD does not affect the Cys C assay; thus, the use of Cys C is proposed for the assessment of renal function levels in patients using CaD. Cys C is commonly used as an indicator for assessing renal function and may be more sensitive than the traditional method [43]. Given that CaD interferes with the enzymatic assay of creatinine, we used Cys C and the GFR calculated using the CKD-EPI Cys C equation to assess renal function.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%
“…However, due to the poor substrate specificity of catalytic peroxidase for the Trinder reaction, multiple substances, such as ascorbic acid [ 1 , 2 ], etamsylate [ 3 ], N-acetylcysteine [ 4 ], and bilirubin [ 5 ], can interfere with the assay’s results. Recently, we confirmed that the medication calcium dobesilate produces significant negative interferences with the determination of creatinine using sarcosine oxidase-based assays, and the extent of interference differs significantly among the different assay systems [ 6 ].…”
Section: Introductionmentioning
confidence: 90%
“…The influence of drugs on the results of clinical testing is a common but often overlooked problem. As described in detail previously [ 6 ], calcium dobesilate (calcium 2,5-dihydroxybenzenesulfonate) is a vasoprotectant [ 7 ] that is widely used to treat diabetic retinopathy [ 8 ], chronic venous insufficiency [ 9 ], and various microangiopathy [ 10 ]. Recent studies have revealed its protective effects on diabetic nephropathy [ 11 ] and gentamicin-induced acute kidney injury [ 12 ] and have suggested potential protective effects against intestinal ischaemia-reperfusion injury by increasing antioxidant capacity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%